Synthesis and Characterization of Poly(aryleneethynylene)s and Their Corresponding Platinum-Linked Polymers - Hossain, M. I.; Debnath, D.; Younis, M.; Bari, M. A.; Miah, M. A. J. (Journal of Scientific Research, 2011)
A series of thermally stable organic polymers [poly(2,5-diethynylpyridine] (5), [poly(1,4- diethynyl benzene)] (6), [poly(2,5-dialkyl-p-phenyleneethynylene)] (7), and [poly(p,p-diethynylbiphenyl)] (8), were synthesized by the reaction between diterminal aryleneethynylene, [HCCArCCH] {Ar = C5H5N (1); Ar = C6H6 (2); Ar = C6H4(CH3)2 (3); Ar = C6H4-C6H4 (4)} and CuCl in pyridine by Hay’s oxidative coupling method. Then the organometallic polymers [Ph (PnBu3)2Pt-C≡C-(Ar-C≡C-C≡C)n-Pt((PnBu3)2Ph] {Ar = C5H5N (9); Ar = C6H6 (10); Ar = C6H4(CH3)2 (11); Ar = C6H4-C6H4 (12)} were synthesized by the reaction of organic polymers 5, 6, 7 and 8 with metal precursor (PnBu3)2 PtPhCl in diethylisopropileamine with good yield. These metal-linked polymers were characterized by IR, 1H-NMR, 13C-NMR and 31P-NMR spectra. Finally the molecular weight of the organometallic polymers (9, 10, 11 and 12) was determined by gel permeation chromatography (GPC). It is clearly observed from GPC that the polymers were synthesized with different degree of polymerization. Keywords: Organometallic polymers; Hay’s Oxidative coupling; GPC. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: 10.3329/jsr.v3i3.7293 J. Sci. Res. 3 (3), 587-597 (2011)